Analgesic and hemodynamic effects of intravenous infusion of magnesium sulphate versus dexmedetomidine in patients undergoing bilateral inguinal hernial surgeries under spinal anesthesia: a randomized controlled study - Inas Farouk; Mohamed Mahmoud Hassan; Ahmed Mohamed Fetouh; Abd Elhay Abd Elgayed; Mona Hossam Eldin; Bassant Mohamed Abdelhamid (Brazilian Journal of Anesthesiology, 2021)
Background: Spinal anesthesia is commonly employed during inguinal hernial surgeries. Its short duration may, however, be considered a limitation, especially for bilateral hernial repair. The aim of this research is to investigate the analgesic and hemodynamic effects of intravenous infusion of both MgSO4 and dexmedetomidine on patients undergoing bilateral inguinal hernia surgeries under spinal anesthesia. Methods: This study was a prospective, randomized, double-blinded controlled trail. It included 60 male patients who had been scheduled for bilateral elective inguinal hernia surgery under spinal anesthesia at Kasr Al-Aini hospital. Patients were randomly allocated to one of three groups (n = 20 each) to receive 50 mL of 0.9% saline intravenous infusion of either dexmedetomidine 0.5 μg.kg-1. h-1 (Group D) or magnesium sulphate 15 mg.kg-1. h-1 (Group M) or normal saline (Group S). The primary outcome of this study was set as the total duration of analgesia. Secondary outcomes were set as the onset and duration of sensory and motor blockade, perioperative hemodynamics, and the total 24-hour postoperative morphine consumption. Results: Durations of sensory and motor blockades as well as durations of analgesia were all significantly longer among patients in Group D (mean 2.2, 3.5, 5.8 hours respectively) and Group M (mean 2.2, 3.3, 5.2 hours respectively), in comparison to Group S (mean 1.5, 2.7, 3.9 hours respectively). No significant differences were found in systolic or diastolic arterial blood pressure, heart rate oxygen saturation, cardiac output, or stroke volume among the study groups. Seven patients in Group D and four patients in Groups M and S developed hypotension. Conclusion: Intravenous infusion of either dexmedetomidine or MgSO4 with spinal anesthesia effectively improves the quality of spinal anesthesia and prolongs the duration of postoperative analgesia and decreases the 24-hour postoperative morphine consumption. Results also demonstrated that the use of dexmedetomidine resulted in a slightly longer duration of analgesia, whilst the use of MgSO4 resulted in slightly better hemodynamic stability.